Bioinformatic and systems biology approach revealing the shared genes and molecular mechanisms between COVID-19 and non-alcoholic hepatitis - Lu, Huishuang; Ma, Jiaxiu; Li, Yalan; Zhang, Jin; An, Yaxin; Du, Wei; Cai, Xuefei (Frontiers in Molecular Biosciences, 2023)
COVID-19 has become a global pandemic and poses a serious threat to human health. Many studies have shown that pre-existing NASH can cause more severe clinical symptoms in patients with COVID-19. However, the potential molecular mechanisms between NASH and COVID-19 are unclear. In this study, we explored key molecules and pathways between COVID-19 and NASH by bioinformatics analysis. We obtained 121 common DEGs between NASH and COVID-19 datasets and constructed a protein-protein interaction network. Two key modules were obtained from the protein-protein interaction network and enrichment analysis of the key modules revealed the common association between NASH and COVID-19. Sixteen hub genes were obtained by five algorithms, and six of them, including KLF6, EGR1, GADD45B, JUNB, FOS and FOSL1 were confirmed to be closely related to NASH and COVID-19. Finally, we performed ssGSEA analysis of six hub genes and constructed the interaction network of six hub genes with TFs, miRNAs, and compounds. Our study identified six hub genes related to COVID-19 and NASH, providing a new perspective for disease diagnosis and drug development.